Gender, blood pressure, and cardiovascular and renal outcomes in adults with hypertension from the Systolic Blood Pressure Intervention Trial. Issue 4 (April 2018) - Foy, Capri G.; Lovato, Laura C.; Vitolins, Mara Z.; Bates, Jeffrey T.; Campbell, Ruth; Cushman, William C.; Glasser, Stephen P.; Gillespie, Avrum; Kostis, William J.; Krousel-Wood, Marie; Muhlestein, Joseph B.; Oparil, Suzanne; et al.
Abstract : Background: To determine if the effects of intensive lowering of systolic blood pressure (goal of less than 120 mmHg) versus standard lowering (goal of less than 140 mmHg) upon cardiovascular, renal, and safety outcomes differed by gender. Methods: Nine thousand three hundred and sixty-one men and women aged 50 years or older with systolic blood pressure of 130 mmHg or greater, taking 0–4 antihypertensive medications, and with increased risk of cardiovascular disease, but free of diabetes, were randomly assigned to either a systolic blood pressure target of less than 120 mmHg (intensive treatment) or a target of less than 140 mmHg (standard treatment). The primary composite outcome encompassed incident myocardial infarction, heart failure, other acute coronary syndromes, stroke, or cardiovascular-related death. All-cause mortality, renal outcomes, and serious adverse events were also assessed. Results: Compared with the standard treatment group, the primary composite outcome in the intensive treatment group was reduced by 16% [hazard ratio 0.84 (0.61–1.13)] in women, and by 27% in men [hazard ratio 0.73 (0.59–0.89), P value for interaction between treatment and gender is 0.45]. Similarly, the effect of the intensive treatment on individual components of the primary composite outcome, renal outcomes, and overall serious adverse events was not significantly different according to gender. Conclusion: In adults with hypertension but not with diabetes, treatment to a systolic blood pressure goal of less than 120 mmHg, compared with a goal of less than 140 mmHg, resulted in no heterogeneity of effect between men and women on cardiovascular or renal outcomes, or on rates of serious adverse events. ClinicalTrials.gov number, NCT01206062. Abstract : Supplemental Digital Content is available in the text